1995
DOI: 10.1207/s15327663jcp0402_02
|View full text |Cite
|
Sign up to set email alerts
|

An Assessment of the Trait Validity of Cognitive Age Measures

Abstract: We extend the concept of cognitive age and assess the internal validity of a direct, multiple‐item approach to its measurement. A multitrait–multimethod matrix consisting of the correlations between average cognitive age, ideal age, and least desired age, as measured by three methods (semantic differential, ratio, and Likert scales), was developed and analyzed using three models: confirmatory factor analysis, correlated uniqueness, and direct product. The correlated uniqueness model performed well in terms of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
0
6

Year Published

2001
2001
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(53 citation statements)
references
References 40 publications
2
45
0
6
Order By: Relevance
“…Overall cognitive age is computed by averaging the midpoint values for the four age dimensions. The cognitive age scale is thus superior to other available instruments on the basis that not only is it multidimensional, it is easy to administer, easy to understand by respondents (Stephens, 1991), has been shown to be a valid instrument (Van Auken, Barry, & Anderson, 1993;Van Auken & Barry, 1995), and has been used successfully across cultures (Barak et al, 2001;Barak, Mathur, Zhang, Lee, & Erondu, 2003;Guiot, 2001;Sudbury, 2004). The reliability of the cognitive age scale was found to be acceptable (Cronbach's alpha 0.89).…”
Section: Methodsmentioning
confidence: 96%
See 1 more Smart Citation
“…Overall cognitive age is computed by averaging the midpoint values for the four age dimensions. The cognitive age scale is thus superior to other available instruments on the basis that not only is it multidimensional, it is easy to administer, easy to understand by respondents (Stephens, 1991), has been shown to be a valid instrument (Van Auken, Barry, & Anderson, 1993;Van Auken & Barry, 1995), and has been used successfully across cultures (Barak et al, 2001;Barak, Mathur, Zhang, Lee, & Erondu, 2003;Guiot, 2001;Sudbury, 2004). The reliability of the cognitive age scale was found to be acceptable (Cronbach's alpha 0.89).…”
Section: Methodsmentioning
confidence: 96%
“…American studies typically report differences between actual and self-perceived age to be between 8 and 12 years (Barak, 1998;Barak & Rahtz, 1999;Sherman, Schiffman, & Mathur, 2001;Van Auken & Barry, 1995), and recent research has found this to be true also for older U.K. consumers (Carrigan & Szmigin, 2000;Sudbury, 2004), although there are a number of studies conducted elsewhere that show the bias toward a youthful self-perceived age to be less pronounced (Chua, Cote, & Leong, 1990;Togonu-Bickerstech, 1986;Uotinen, 1998).…”
Section: Self-perceived Agementioning
confidence: 99%
“…In contrast, Barak (1998) found chronological, cognitive, and desired ages to differ in a consistent pattern with mean chronological age older than that of cognitive age and mean age-of-birth even older than that of desired age. As mentioned earlier, Uotinen (1998) found differences between male and female desired-age perception, yet she also reports that Finns exhibit some of the same age denial as Americans.Research in a variety of U. S. populations supports the finding that chronological age and cognitive-and desired-age dimensions interrelate positively (Barak, 1987(Barak, , 1998 Barak & Stern, 1995/86, 1986aBarak et al, 1988;Van Auken & Barry, 1995). This research implies that the older one's real age, the older one's cognitive-and desired-age concepts, which is particularly true when one considers membership in self-ascription age groupings such as young and middle-aged.…”
mentioning
confidence: 86%
“…Cognitive age may remain static for a number of years until a major life occurrence (Van Auken and Barry, 1995) and it makes market segmentation using cognitive age as a variable particularly attractive. Investigating cognitive age may provide marketers with a better grasp of how mature consumers see themselves, their attitudes and consequently their shopping behaviour (Bone, 1991;Van Auken and Barry, 1995;Van Auken and Lonial, 1991). Behling (1999) suggests that females aged over 45 still see themselves in the same way they did when younger.…”
Section: Cognitive Versus Chronological Agementioning
confidence: 99%